If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
6-((1/3)*x)-3 = (-1/2)*x // - (-1/2)*x
6-((1/3)*x)-((-1/2)*x)-3 = 0
(-1/3)*x+(1/2)*x-3+6 = 0
1/6*x+3 = 0 // - 3
1/6*x = -3 // : 1/6
x = -3/1/6
x = -18
x = -18
| 42x^2+x=1 | | 3j-5=13 | | 1/4*12m | | 8x^2-6x-12=0 | | (143)(y)=6 | | 0.6x+11=0.8x-1 | | 9+2t=17 | | 9y-85=7(4+y) | | 14u=24+8u | | 4(x+3y+5)+2(x-1)= | | Y=2x+24x-16 | | 143xy=6 | | 22q=792 | | 9s-12=33 | | -623=u+107 | | 0.04Xy=24 | | 2x-3-4lnx=0 | | 1=0.2x-0.9x-27 | | -27=6-3p | | 4x+9x-5=138 | | 3x+1x=4x+6x-6x | | c+819=-106 | | -3t+2t-10=-2 | | 10-12y+5=2(y-8) | | -733=w+-425 | | 2x^2+9=109 | | 4n-8=-40 | | 10t+5t+t-15t=12 | | 5(x)=2x-10 | | x^2-2x+y^2-6y=-6 | | Log(6x-8)=0 | | 0(x)=2x-10 |